Environmental attitude: values on urban wildlife a case study of Kuala Lumpur Urban Parks - Hj. Baharuddin, Zainul Mukrim (Edinburgh Architecture Research, 2013)
‘Urban biodiversity and wildlife management’ has been accepted as being an important urban ecological component in an urban environment. The improvement of urban plans and landscape fabric can potentially advance the urban ecological environment. Thus, many local authorities aim to outline green strategies in their local plans to improve the city’s health. However, the study of urban biodiversity and its relation to the human dimension is not well explored by researchers. Miller (2003) and Jones et al. (1998) argue that there is a lack of empirical research leading to inconclusive knowledge in this field. ‘Human dimension’ is the study of integration between the social dimension and existing ecological information. This paper aims to investigate environmental attitudes on urban biodiversity especially on urban wildlife in Kuala Lumpur. It assesses the potential of ‘human dimension’ in realising planning objectives in Kuala Lumpur. The research will investigate the links and relationships between demographic factors and values with regard to urban biodiversity. Information collected through a questionnaire survey is the informational basis of this study. The survey focused on two major groups, namely stakeholders (n = 128) and residents (n = 288). The results indicated that people who lived close to Kuala Lumpur urban parks had higher moralistic values towards urban wildlife. Naturalistic, ecologistic and scientific values had mean scores between 3.5 and 4.0, which could be considered as an acceptable degree of agreement. Most respondents placed higher values on wildlife and its ecosystems. Other values such as negativistic, humanistic, utilitarian and dominionistic values had mean scores between 2.5 and 3.00 indicating that these values depend on specific issues and situations related to urban wildlife. It could be inferred that people in Kuala Lumpur do not have strong negativistic, humanistic, utilitarian and dominionistic values towards urban wildlife. This research will help in improving green urbanism strategies, to achieve sustainable living environments.